2011
DOI: 10.1016/j.taap.2011.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal administration of the cytochrome P4501A inducer, Β-naphthoflavone (BNF), attenuates hyperoxic lung injury in newborn mice: Implications for bronchopulmonary dysplasia (BPD) in premature infants

Abstract: Supplemental oxygen contributes to the development of bronchopulmonary dysplasia (BPD) in premature infants. In this investigation, we tested the hypothesis that prenatal treatment of pregnant mice (C57BL/6J) with the cytochrome P450 (CYP)1A1 inducer, β-napthoflavone (BNF), will lead to attenuation of lung injury in newborns (delivered from these dams) exposed to hyperoxia by mechanisms entailing transplacental induction of hepatic and pulmonary CYP1A enzymes. Pregnant mice were administered the vehicle corn o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 62 publications
(94 reference statements)
3
38
0
Order By: Relevance
“…These results parallel those observed in other hyperoxic lung injury animal models (2,6,24,27,32) as well as what is clinically observed (16). These changes represent a lung developmental arrest, typically characterized by a simplification with enlarged alveoli and thickened septa (6,24,27,32).…”
Section: Discussionsupporting
confidence: 88%
“…These results parallel those observed in other hyperoxic lung injury animal models (2,6,24,27,32) as well as what is clinically observed (16). These changes represent a lung developmental arrest, typically characterized by a simplification with enlarged alveoli and thickened septa (6,24,27,32).…”
Section: Discussionsupporting
confidence: 88%
“…Each sample was analyzed in duplicate. The relative Ct values for CYP1A1, 1A2 and CYP1B1 were normalized to their 18S content and the relative expression levels of target genes were calculated according to the equation, 2 −ΔΔCT , where ΔΔCT=ΔCt target gene−ΔCt control gene, as reported by us previously (Couroucli et al, 2006; 2011). …”
Section: Methodsmentioning
confidence: 99%
“…The molecular mechanisms by which hyperoxia causes lung injury are not understood, but CYP enzymes have been implicated (Hazinski et al, 1995). On the other hand, studies from our laboratory have demonstrated the protective effect of CYP1A enzymes against hyperoxic lung injury (Couroucli et al, 2011; Couroucli et al, 2002; Jiang et al, 2004; Moorthy et al, 2000; Sinha et al, 2005); Moorthy, 2008). However, there have been no studies on the effect of maternal exposure of environmental PAHs on hyperoxic lung injury in the offspring.…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, recent studies have demonstrated an attenuating effect of CYP1A1 inducers on hyperoxic lung injury both in vitro [10,24] as well as in vivo [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the importance of cytochrome P450 enzymes as well as the aryl hydrocarbon receptor (AhR) has been demonstrated in the metabolism of a number of endogenous and exogenous compounds as well as for oxygen-induced toxicity [10][11][12][13]. When a ligand binds, AhR is translocated to the nucleus, where it dimerizes with the aryl hydrocarbon nuclear translocator (ARNT).…”
mentioning
confidence: 99%